The Effect of Street Orientation on the Temporal Variation in Thermal Environment Within Streets in Different Climate Zones - Jiayu Li; Jifa Rao; Lan Wang (Buildings)
Orientation is a key indicator affecting the street thermal environment, especially by modifying the radiation temperature. Comprehending the temporal variation in the thermal environment helps in adapting to heat exposure on streets with different orientations. Existing studies have revealed the impacts of street orientations on static thermal environments, namely, the thermal environment at a location at a certain time. However, the thermal environment is dynamically changing, yet the impact of the street orientation on this dynamic change has not yet been revealed, which is an important reference for citizens to choose appropriate streets and exposure times. This study takes the typical cities in China as examples. By simulation, the thermal data of each hour within the street were collected. Then, the thermal distribution map was initiated to display the temporal variation in the thermal environment in various oriented streets. Finally, for each oriented street, the regulatory capabilities, as well as the impacts on “hot” perception, were analyzed. Specifically, the maximum regulatory capabilities of the street orientation on PETs were about 3 °C (Harbin), 5 °C (Xi’an), 11 °C (Changsha), 10 °C (Guangzhou), 4 °C (Kunming), 4 °C (Xining), and 6 °C (Urumqi). Furthermore, taking 39 °C as the marker of “hot” PET perception, the regulatory capabilities of the street orientation on the period of “hot” perception were approximately 1 h (Harbin), 2.5 h (Xi’an), 2.5 h (Changsha), 1.5 h (Guangzhou), 5 h (Kunming), 1 h (Xining), and 5 h (Urumqi).